2017
DOI: 10.1007/s40271-017-0255-7
|View full text |Cite
|
Sign up to set email alerts
|

Does Patient Preference Measurement in Decision Aids Improve Decisional Conflict? A Randomized Trial in Men with Prostate Cancer

Abstract: Individual-level preference assessment is feasible in the clinic setting. Patients with prostate cancer who undergo preference assessment are more certain about their treatment decisions and report decreased levels of decisional conflict when making these decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Prior efforts to identify factors associated with treatment choice using data limited to patient demographics and tumor characteristics (fixed factors) have struggled to adequately explain patient decision making ( 15 ). Prior studies investigating patient treatment preferences have suggested that incorporating patient preferences for values and goals ( 16 , 17 ) and shared decision making ( 18 , 19 ) may help guide patient treatment choices. The current study confirms that patient-reported decision factors substantially improve the ability to discriminate between those making and those not making aggressive treatment choice for a low-risk disease.…”
Section: Discussionmentioning
confidence: 99%
“…Prior efforts to identify factors associated with treatment choice using data limited to patient demographics and tumor characteristics (fixed factors) have struggled to adequately explain patient decision making ( 15 ). Prior studies investigating patient treatment preferences have suggested that incorporating patient preferences for values and goals ( 16 , 17 ) and shared decision making ( 18 , 19 ) may help guide patient treatment choices. The current study confirms that patient-reported decision factors substantially improve the ability to discriminate between those making and those not making aggressive treatment choice for a low-risk disease.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding what factors influence preference is important in the context of assisting patients make appropriate decisions with regards to their treatment. In a randomized controlled trial comparing standard patient education with or without preference measurement in 122 men with prostate cancer, those patients who underwent preference assessment were more certain about their treatment decisions and reported decreased levels of decisional conflict [37]. Similar benefits of shared decision-making have been reported for lung cancer [38] and breast cancer [39].…”
Section: Discussionmentioning
confidence: 90%
“…Preference assessment may also improve medical decision making 11,27,28 . In the absence of preference assessment of patients, physicians may substitute their own preferences or beliefs about the patient’s preferences, which can lead to suboptimal treatment decisions 29 , 30 .…”
Section: Why Are Patient Preferences Important?mentioning
confidence: 99%